DEVELOPING A LISTENING-SPEAKING TECHNIQUE FOR ELEMENTARY SCHOOL STUDENTS BASED ON A â€œLEM-LEM TAKâ€ GAME - Aprisama, Sigit; ., Ikhsanudin; ., Sudarsono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract:The purpose of this study is to develop listening-speaking techniqueforelementary school. Development research was used in this study, and model that was used based on ADDIE model. The data were collected through observation, interview, content analysis, focus group discussion, and from the experts’ validation. The participants of this study werea primary English language teacher and thestudents of SD Negeri 17Singkawang Tengah Grade 5. The results of this study revealed that the teaching technique was needed by the teacher, the students, the school, and the curriculum of SD Negeri 17 Singkawang Tengah. This teaching technique also could make students learn actively during their learning. The experts also recommended this teaching technique could be used in teaching English to the elementary school students. It can be concluded that the teaching technique is effective to improve students’ activeness during their learning and recommended by the experts. Key Words: Elementary School, Development Research, ADDIE Abstrak:Penelitian ini bertujuan untuk mengembangkan teknik mengajar speaking dan listening pada mata pelajaran bahasa Inggris di jenjang sekolah dasar. Penelitian ini menggunakan metode penelitian pengembangan, dan model yang digunakan adalah model ADDIE. Data diperoleh melalui observasi, wawancara, analisis isi, diskusi kelompok, dan validasi ahli. Partisipan dari penelitian ini adalah guru bahasa Inggris dan siswa kelas 5 SD Negeri 17 Singkawang Tengah. Hasil penelitian menunjukkan bahwa teknik mengajar ini diperlukan oleh guru, siswa, sekolah, dan sesuai dengan kurikulum SD Negeri 17 Singkawang Tengah. Tehnik mengajar ini juga dapat meningkatkan keaktifan siswa selama belajar. Para ahli juga merekomendasikan bahwa tehnik mengajar ini dapat digunakan untuk mengajar bahasa Inggris di jenjang sekolah dasar. Dapat disimpulkan bahwa tehnik ini efektif untuk meningkatkan keaktifan siswa selama belajar dan direkomendasikan oleh para ahli. Kata Kunci: Sekolah Dasar, Penelitian Pengembangan, ADDIE